COMORBIDITY IN RHEUMATOID ARTHRITIS - T. A. Panafidina; L. V. Kondratyeva; E. V. Gerasimova; D. S. Novikova; T. V. Popkova (Научно-практическая ревматология, 2014)
The peak onset of rheumatoid arthritis (RA) is at 30-55 years of age. At this age, the patients have also other concomi- tant diseases (comorbidities) that affect the course and prognosis of RA, the choice of its treatment policy, quality of life of the patients. Objective: to identify the most important and common comorbidities in patients with RA. Subjects and methods. Two hundred patients (median age 55 [46; 61] years) were enrolled; there was a preponderance of women (82.5%) with median disease duration 5 [1; 10] years, seropositive for IgM rheumatoid factor (83.0%) and anti-cyclic citrullinated peptide antibodies (81.6%) with moderate and high disease activity (median DAS28 value 3.9 [3.1; 4.9]). Varying degrees of destructive changes in hand and foot joints were radiologically detected in 71.2% of the patients; 64.5% of the patients had Functional Class II. Methotrexate was given to 69.5% of the patients; therapy with biological agents was used in 21.0% of the cases. 15.5% of the patients did not receive DMARD or biologics. 43.0% of the patients with RA received glucocorticoids. Results. Comorbidities were present in 72.0% of the patients with RA. The most common diseases were hypertension (60.0%), dyslipidemia (45.0%), fractures at various sites (29.5%), and coronary heart disease (21.0%). Myocardial infarction and stroke were observed in 1.5 and 1.0% of cases, respectively. There was diabetes mellitus (DM) in 7.5% of the cases and osteoporosis in 15.5% of the patients. 81.7% of the patients with RA and hypertension and 80.0% of those with RA and DM received antihypertensive and sugar-lowering therapy, respectively. At the same time the RA patients with dyslipidemia and osteoporosis received specific drugs far less frequently (30.0 and 29.0%, respectively). Conclusion. Comorbidities are frequently encountered in RA. By taking into account the fact that cardiovascular dis- eases are a main cause of death in RA; it is necessary to adequately and timely modify traditional risk factors (hyper- tension, dyslipidemia, and diabetes mellitus). Treatment patients with RA requires an interdisciplinary approach and an interaction between physicians of different specialties.